Dynamics of Destructive Joint Changes in Juvenile Idiopathic Arthritis in Children who Received Methotrexate or Methotrexate-Tocilizumab Combination: a Cohort Study - Maria A. Davydova; Galina V. Santalova; Elena R. Stadler; Elena S. Gasilina (Вопросы современной педиатрии)
Background. Destructive joint damages in juvenile arthritis inevitably lead to persistent disability in adulthood. These consequences can be avoided by resorting to early therapy of the disease.Objective. Our aim was to assess the dynamics of destructive joint changes in juvenile idiopathic arthritis (JIA) in children, depending on a basic therapy.Methods. We studied the treatment results of children with systemic-onset JIA with active joint syndrome without active  systemic manifestations hospitalized in the regional clinical  cardiological health center. JIA activity criteria at the time of  hospitalization: 3 joints with active arthritis; the assessment of the disease activity by a doctor 3 points out of 10; the assessment of  wellbeing by the patient or a parent 3 points out of 10; the  appointment of basic therapy no later than 6 months from the  disease onset. Treatment results were compared in the groups of  methotrexate (hospitalization from January 2008 to December 2010) and methotrexate + tocilizumab (January 2014 — September 2016). The main outcome of JIA therapy was the severity of joint  destruction in 6, 12 and 24 months as determined by the modified  Sharpe ratio according to radiographs obtained from patients' medical records.Results. The study groups were comparable in terms of sex and age of the patients, JIA onset age, the disease activity at the time of  hospitalization, and the initial assessment of joint destruction —  (median) 165 (131; 187) and 162 (124; 171) (p = 0.116). Under  pressure of therapy, the modified Sharpe score in the group of  methotrexate monotherapy was higher than in the group of combined therapy: in 6 months — 142 (126; 163) and 87 (72; 112) (p < 0.001); in 12 months — 166 (121; 210) and 75 (29; 89) (p <  0.001); in 24 months — 165 (113; 198) and 52 (26; 73) (p <  0.001). At the first administration of tocilizumab, 4 children had nausea and abdominal pain, and 3 children had headache.Conclusion. Basic therapy with methotrexate and tocilizumab  inhibits the destruction of joints in patients with systemic-onset JIA  with active joint syndrome without active systemic manifestations.